Pott’s Paraplegia in a 2 Years Female: A Rare Presentation at an Early Age - Preeti Basnet; Anish Joshi; Saurab Karki; Anil Jung Thapa; Prayash Poudel; Anugya Sapkota; Manoj Shrestha; Shreebridhi Pande (Case Reports in Infectious Diseases)
Introduction. Potts disease is extrapulmonary skeletal tuberculosis mostly affecting the thoracolumbar spine. It destroys the disc space, adjacent vertebral bodies, and spinal elements, leading to cord compression and paraplegia. Methods. This is a case report study of a 29-month-old toddler who presented to our hospital with bilateral lower limb weakness. Results. On clinical, laboratory, and radiological examination, she was diagnosed with Pott’s spine, started on antitubercular therapy, and planned for surgery in her follow-up. Conclusion. Tuberculosis of the spine is still prevalent in developing countries, mainly in children. Complications of the disease can be devastating because of its ability to cause bone destruction, spinal deformity, and paraplegia. So, in a tuberculosis-endemic region, clinical suspicion should be there for Potts disease when a child presents with paraplegia of the lower limbs. Children can develop tuberculosis which can spread to the spine despite vaccination. The prognosis of spinal tuberculosis is improved by early diagnosis and rapid intervention.